A comparison of self-reported sickness absence with absences recorded in employers' registers: evidence from the Whitehall II study. Issue 2 (18th January 2005) - Ferrie, J E; Kivimäki, M; Head, J; Shipley, M J; Vahtera, J; Marmot, M G
Abstract : Aim: To compare self-reported sickness absence days in the last 12 months with recorded absences from the employers' registers for the same period. Methods: Self-reported sickness absence data over the 12 months preceding baseline (1985–88) were compared with absence records from the employers' registers over the same period for 2406 women and 5589 men, participants in the Whitehall II study of British civil servants. Associations with self-rated health, longstanding illness, minor psychiatric disorder, physical illness, and prevalent coronary heart disease at baseline were determined. Results: In general, women reported less sickness absence over the last year than was recorded in the employers' registers, while men, with the exception of those in the lower employment grades, reported more. Agreement between self-reported and recorded absence days decreased as the total number of days increased. After adjustment for employment grade and the average number of recorded and self-reported absence days, the total number of self-reported absence days was within two days of the recorded number of days for 63% of women and 67% of men. Associations between annual self-reported sickness absence days and self-rated health, longstanding illness, minor psychiatric disorder, physical illness, and prevalent coronary heart disease were as strong as those for recorded absence days. Conclusion: These findings suggest that agreement between the annual number of self-reported and the annual number of recorded sickness absence days is relatively good in both sexes and that associations with health are equivalent for both measures.